2019
DOI: 10.1111/jace.16909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation vacancies on the optical and dielectric properties of KSr2Nb5O15: A first‐principles study

Abstract: Using first‐principles calculations, the effect of cation vacancies on the electronic structures and optical characters of KSr2Nb5O15 (KSN) lead‐free ferroelectrics are investigated. The calculated dielectric properties are demonstrated by the experimental results. The cation vacancies involve K+ vacancies (KSN‐K), Sr2+ vacancies (KSN‐Sr), and coexisting K+ and Sr2+ vacancies (KSN‐K&Sr). When these cation vacancies exist in KSN, the unit cell volumes decrease, leading to phase transition from tetragonal to ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The band structures of KSN‐Nb1 and KSN‐Nb2 are shown in Figure 4 . When comparing the PDOS and band structure of defect‐free KSN [ 9 ] with those of KSN‐V B , the PDOS and band structures of KSN with Nb 5+ vacancy show significant differences. When the Nb1 and Nb2 sites of KSN are vacant, the bandgap of KSN‐Nb1 remains indirect, the bandgap generates between the Q point (valence band) and the F point (conduction band), whereas KSN‐Nb2 becomes a direct bandgap compound, the bandgap generates between the G point (valence band) and the G point (conduction band).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The band structures of KSN‐Nb1 and KSN‐Nb2 are shown in Figure 4 . When comparing the PDOS and band structure of defect‐free KSN [ 9 ] with those of KSN‐V B , the PDOS and band structures of KSN with Nb 5+ vacancy show significant differences. When the Nb1 and Nb2 sites of KSN are vacant, the bandgap of KSN‐Nb1 remains indirect, the bandgap generates between the Q point (valence band) and the F point (conduction band), whereas KSN‐Nb2 becomes a direct bandgap compound, the bandgap generates between the G point (valence band) and the G point (conduction band).…”
Section: Resultsmentioning
confidence: 99%
“…This means that when the Nb 5+ vacancy is generated, the point defect formed is (normalVNb5+normale+3normalVnormalO2·), (normalVNb5+normalVnormalK+3normalVnormalO2·), (normalVNb5+normalVSr2+normalVnormalK+4normalVnormalO2·), or (2normalVNb5+2normalVSr2+7normalVnormalO2·). According to the results of the vacancy formation energy of the presence of cationic vacancies in the KSN, [ 9 ] K + and O 2− form a weak ionic bond, Sr 2+ and O 2− form a weak covalent bond, and Nb 5+ and O 2− form a strong covalent bond; so, the E f of K + vacancy in KSN is the lowest and K + vacancy is the easiest to produce, followed by Sr 2+ vacancy, K + and Sr 2+ vacancies coexistence, and Nb 5+ vacancy is the most difficult to produce. However, according to a recent research on the microstructure and electrical performance of KSN, energy dispersive spectroscopy (EDS) analysis of KSN microcrystalline powder and ceramic revealed that K + and Sr 2+ vacancies exist in KSN, with a tiny quantity of Nb 5+ vacancies remaining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation